Nonlinear association between ownership concentration and leverage: The role of family control - Lo H.-C.; Ting I.W.K.; Kweh Q.L.; Yang M.J. (Elsevier Inc., 2023)
The 2008-2009 global financial crisis and the European debt crisis have raised further questions on leverage decision making. In this regard, this study examines the association between concentration of controlling rights and leverage in the presence of families. This study also assesses the role played by families in moderating the nonlinear reversed U-shaped association between concentration of controlling rights and debt ratio. Publicly listed companies in Taiwan, which is a nation characterized by weak protection for minority shareholders, are studied for the period of 1999 to 2014. The effect of the nonlinear inverted U shape is confirmed, and the weakened effect of the existence of family control is presented. The results remain unchanged in several alternative tests, including addressing the endogeneity issue of ownership-decision studies. Overall, this study highlights the ownership-debt relationship in a nation with weak protection of minority shareholders. 2016 Elsevier Inc.